Retrofitting design of Kathmandu University library building after Gorkha earthquake 2015 - P. M. Pradhan; R. Adhikari; A. Dahal; A. Shrestha; D.L Subedi; S. Thapa; P. Kharel (Lowland Technology International, 2016)
The major earthquake on April 25, 2015 (7.8 Mw) and the aftershock on May 12, 2015 (7.3 Mw) caused severe damages on Kathmandu University (KU) Library. Disaster prevention of the library building is necessary to restore its strength and reduce seismic risk. Retrofitting approach can be employed to strengthen the building and increase its seismic capacity. Seismic retrofit is an effective technique by which the building can be strengthened to improve its seismic performance without affecting its aesthetics value and architectural identity. To achieve public safety by considering use of various materials and structural stability, retrofitting is economically applied to meet functional and structural requirements of the building. This pro-active disaster mitigation technique has been effective in modifying the existing structure for strengthening to improve its structural performance.